Open visitation in a neonatal intensive care unit: visitors’ perception - Ana Luiza da Costa Cunha; Nilba Lima de Souza; Rafaela Maria Alves da Rocha Rêgo; Ana Celly Bezerra Cruz Paiva dos Santos; Cecília Olívia Paraguai de Oliveira; Jéssica Maria Arouca de Miranda (Rev Rene)
This study aimed to identify the perceptions of parents, caregivers and visitors about the open visitation to newborns hospitalized in the Neonatal Intensive Care Unit. This is a descriptive, quantitative study, involving 50 visitors of newborns hospitalized in the neonatal unit of a school maternity hospital from Natal-RN, from October to December 2012. The data were collected through a questionnaire with closed questions, from which after data analysis, it was observed that most of the fathers, with the exception of family visitors, had free access to the unit, they considered to be well accepted by the staff and the information about the clinical condition of newborns was satisfactory. Most were welcomed and guided by the nurse, and were encouraged to come back for another visit. All of them considered important to visit the mother and the newborn, highlighting the need for bigger integration among professionals and family members.